Gender and Teaching Age as Determinants of Teachers' Professional Identity: Insights from South Korea and Indonesia - Nurdin Akhmad, Sudaryat; Aulia Nadhirah, Nadia; Iskandar Pratiwi, Tiara; Nunyuia Amedome, Sedem; Hartanto, Dody; Ilfiandra, Ilfiandra (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The study examines teachers' professional identity by gender and teaching age using an explanatory survey with 196 participants from South Korea and Indonesia. Using a 25-item Likert scale, four dimensions were measured: job satisfaction, work commitment, motivation, and self-efficacy. Multivariate analyses showed no significant overall difference in professional identity between teachers from the two countries. However, South Korean teachers reported lower job satisfaction but higher self-efficacy compared to Indonesian peers. Gender did not influence professional identity overall, though male teachers in both countries tended to have higher job satisfaction than females. No interaction was found between country and gender. Teaching age did not generally affect professional identity, but an interaction effect with country was observed for self-efficacy: South Korean teachers showed a convex pattern across three teaching age categories, whereas Indonesian teachers showed a concave pattern, consistently lower than South Korean counterparts. These findings highlight cross-national differences in components of professional identity and suggest implications for theory and practice in teacher professional development, emphasizing the need to consider cultural and experiential factors in identity formation. This contributes to understanding how personal and contextual variables shape teachers' professional self-concept in varying educational settings. Keywords: explanatory survey, gender, identity formation, professional identity, teaching age